Constructivism of Neurosains-Based in Building the Qur'ani Character of Smp Muhammadiyah I Sleman Students - Saibah; Suyadi (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2020)
The character of the Quran is formed to foster a good self-awareness of the child both in terms of character, honesty and discipline.The aim of this research is the implementation of the Alquran Read and Write program to the change in the character of students who are expected to become individuals who have the character of the Quran. BTAQ learning is carried out using the theory of constructive which involves the concept of neuroscience theory. This study uses descriptive qualitative by taking data through several stages, namely observation, interviews and documentation. Based on research that has kbeen conducted by researchers that Read the Qur'an is an effective way to develop children's character, starting with the habit of reading the Quran and understanding the values in the Quran.